Does the UK government's teenage pregnancy strategy deal with the correct risk factors? Findings from a secondary analysis of data from a randomised trial of sex education and their implications for policy. Issue 1 (20th December 2006) - Allen, E; Bonell, C; Strange, V; Copas, A; Stephenson, J; Johnson, A M; Oakley, A
Abstract : Background: Much of the UK government's 1999 report on teenage pregnancy was by necessity based on rather old or non-longitudinal research. Aim: To examine the associations between risk factors identified in the report and pregnancy at or before age 16 years among young women and partners of young men using the more recent data. Results: Socioeconomic disadvantage, being born to a teenage mother, expectation of being a teenage parent, low educational expectations and various other behaviours are potential risk factors for teenage pregnancy, as suggested by unadjusted analyses. Those who cited school as providing information on sex had a reduced risk of pregnancy at or before age 16 years, as did girls reporting easy communication with parent or guardian at baseline. Various measures of low sexual health knowledge were not associated, in either adjusted or unadjusted analyses, with increased risk of pregnancy at or before age 16 years among boys or girls. Conclusions: A focus on many of the risk factors identified in the 1999 report is supported herein. It is suggested that knowledge may not be an important determinant, but that relationships with parents and school, as well as expectations for the future, may have important influences on teenage pregnancy. The analysis also provides new insights into risk factors for pregnancies among the partners of young men.